PENGARUH BRAND IMAGE DAN STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMEN PADA DISTRO INSPIRED27 KOTA MALANG Distro Inspired27, Jl. Soekarno Hatta D 511, Kota Malang - Febianto, Windu; Pradana, Bayu Ilham (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to identify and analyze the Influence of Brand Image and Store Atmosphere Of Interest Buy Consumer to Distro Inspired27 In Malang, and  in this study used the Partial Test and Simultaneous Test. This type of research is correlational research  that explains the causal relationship between the variables through hypothesis testing.In this study used a sample of 300 respondents drawn from the population of adolescents aged 15 to 30 years old in the city of Malang who ever bought or visiting to Distro Inspired27. Sampling using accidental  sampling technique using certain considerations, generally tailored to the criteria, or objectives of this research problem. To determine the magnitude of the relationship and the influence of the independent variables on the dependent variable used Model Regression Analysis, while to test the hypothesis using the t test and F test.The results showed that the results of the  statistical calculation results obtained coefficient of determination (adjusted R2) of 41.5%. That is the variable brand image and store atmosphere provides an explanation of 41.5% of consumer buying interest on distributions Inspired27. Partial test shows that the brand image variables are not significantly influence consumer buying interest and a variable store atmosphere significantly influence consumer purchasing request on Inspired27 distributions. However, simultaneously the two variables influence on consumer buying interest on Distro Inspired27. Keywords: Brand Image, Store Atmoshere, and Consumer Interest Buying.